Want2B: an Entrepreneurial Learning Menu - Orvalho, Luísa (2009)
The project Want2B aims to disseminate and transfer methods, practices, tools and experiences to promote a wide range of entrepreneurial pedagogical methods and delivery systems, thus supporting an entrepreneurial mindset and culture in the individual and in organisations.